Nexus between Fuel Prices and Energy Consumption in ASEAN Region: Role of Coal, Gas and Oil Prices - Tarasawatpipat, Chaisri; Mekhum, Witthaya (International Journal of Energy Economics and Policy, 2020)
Energy consumption is considered as one of the most important sectors for revenue generation for the state. The revenue generation has tended to be limited for this consumption sector. For this purpose, this study investigates the problem by focusing on the factors like coal prices, gas prices and oil prices as they determine the energy demand’s price elasticity. This effect and change in energy demand to the difference in prices can impact the revenue generation in the country. The data has been collected over a period of 30 years from 10 ASEAN countries including Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, Philippines, Singapore, Thailand, and Vietnam. The independent variables are coal price, gas price and oil price and their effect are measured on the energy consumption. The control variables included are non-renewable energy consumption and population growth of these countries. For this purpose, we have used pooled mean group (PMG) and Augmented Dickey Fuller (ADF) technique along with unit root tests and the cointegration tests among the variables. The results indicate that gas price, oil price, and coal price significantly impact the fuel prices and the energy consumption in these countries. Keywords: Energy Consumption, Coal Price, Gas Price, Oil Price, ASEAN Countries JEL Classifications: K32, L95 DOI: https://doi.org/10.32479/ijeep.10452